ln(x-1)+ln(x+1)-2ln(x)=0

Simple and best practice solution for ln(x-1)+ln(x+1)-2ln(x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x-1)+ln(x+1)-2ln(x)=0 equation:


Simplifying
ln(x + -1) + ln(x + 1) + -2ln(x) = 0

Reorder the terms:
ln(-1 + x) + ln(x + 1) + -2ln(x) = 0
(-1 * ln + x * ln) + ln(x + 1) + -2ln(x) = 0
(-1ln + lnx) + ln(x + 1) + -2ln(x) = 0

Reorder the terms:
-1ln + lnx + ln(1 + x) + -2ln(x) = 0
-1ln + lnx + (1 * ln + x * ln) + -2ln(x) = 0
-1ln + lnx + (1ln + lnx) + -2ln(x) = 0

Multiply ln * x
-1ln + lnx + 1ln + lnx + -2lnx = 0

Reorder the terms:
-1ln + 1ln + lnx + lnx + -2lnx = 0

Combine like terms: -1ln + 1ln = 0
0 + lnx + lnx + -2lnx = 0
lnx + lnx + -2lnx = 0

Combine like terms: lnx + lnx = 2lnx
2lnx + -2lnx = 0

Combine like terms: 2lnx + -2lnx = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| x+2-8x=-3x | | x+2-8x=3x | | x+2-8x=6x | | x+2-8x=5x | | -1.4x+y+z=0 | | X^2+5x=1982 | | -1(-3b-2)=11 | | X^2+x=1990 | | X^2+x=1991 | | x+(2y-3x+5y)= | | 2f+3=2f-3 | | 10d-40=140-2d | | 3p(p-8)= | | 5b+3=3b+5 | | x=0.75y | | √(0.49/0.25) | | 12x-18y=-24 | | 2.x=10 | | 8x+11=7-4x | | =0.75 | | 900=0.75 | | e=0.75 | | ln(x-1)+ln(x-2)=ln(x+2) | | x+(x+3)=3x-5 | | 3690*x=1539554 | | -2(-9-p)=9 | | (x+1)(x+2)(x+3)=5 | | 3c-35=3 | | 12-f=9 | | X+z=9 | | -4b+b+-4=3 | | 3y+z=8 |

Equations solver categories